Rascunhos impressos em verde: reflexões sobre a chegada do ambientalismo em Pacoti-CE - Santos, Javan Pires dos (2008)
This paper presents some relationships emerged or reinforced through contact between residents of the city of Pacoti, in the state of Ceará, and the environmentalism originated after the law which turns the city into part of the Environment Protection Area of Baturité. The perspective adopted uses, mainly, some terms from the Pierre Bourdieu’s sociology – habitus, field, cultural arbitrary, and pedagogic action – and the notion of “modernity without modern rationality” in which José de Souza Martins writes some elements for Brazilian cultures. The empiric study was done in Pacoti and contains the material recorded through direct observation on field and open interviews with 14 people who live or work in the city. The trips for the research occurred in two moments: from March to October, 2005 – still as part of another research – and from September, 2007 to April, 2008. The discussion of this paper is divided into two steps: first a brief reflection about how the thought and the environmentalism action turned into a modern phenomenon and creator of social conflicts. The second step discusses how this environmentalism is appropriated or rejected by the interviewees, which also works as a preliminary diagnostic instrument of the concrete possibilities of operating a Conservation Unit of Sustainable Use, as is the case of the Baturité’s APA. In the end was possible to notice that beyond the large amount of appropriation and derivations from environmentalism in the city, there is a clear connection between it and the replacement of the social-cultural local system based on the rural production for another system based on the tourist leisure.